Detection of Rickettsia RaoultiI Genotypes in Southern Kazakhstan - I. E. Samoylenko; L. V. Kumpan; N. A. Okolelova; Y. P. Igolkina; A. Yu. Tikunov; V. A. Rar; R. A. Egemberyeva; A. N. Kolomeetz; T. A. Reshetnikova; N. V. Rudakov (Эпидемиология и вакцинопрофилактика, 2016)
Previously it was established that different species of genus Rickettsia were detected in Kazakhstan. Nevertheless, rickettsial species spectrum of some regions of Kazakhstan has not been studied. Dermacentor niveus ticks from Southern Kazakhstan were investigated using cell cultures by shell vial technique. The first isolates close related to genotypes Rickettsia raoultii RpA4 and DnS14 were obtained. The role of these agents in tick-borne rickettsioses morbidity in Southern Kazakhstan is discussed.